Sequential injection chromatography with an ultra-short monolithic column for the low-pressure separation ofα-tocopherol and γ-oryzanol in vegetable oils and nutrition supplements - Thaithet S. (2017)
© 2017, The Japan Society for Analytical Chemistry. A low-pressure separation procedure of α-tocopherol and γ-oryzanol was developed based on a sequential injection chromatography (SIC) system coupled with an ultra-short (5 mm) C-18 monolithic column, as a lower cost and more compact alternative to the HPLC system. A green sample preparation, dilution with a small amount of hexane followed by liquid-liquid extraction with 80% ethanol, was proposed. Very good separation resolution (R s = 3.26), a satisfactory separation time (10 min) and a total run time including column equilibration (16 min) were achieved. The linear working range was found to be 0.4 - 40 μg with R 2 being more than 0.99. The detection limits of both analytes were 0.28 μg with the repeatability within 5% RSD (n = 7). Quantitative analyses of the two analytes in vegetable oil and nutrition supplement samples, using the proposed SIC method, agree well with the results from HPLC.